The relationship of morphology and motor abilities to specific table tennis tasks in youngsters - Nikolic, I.; Furjan-Mandic, G.; Kondric, M. (Collegium Antropologicum, 2014)
The aim of this research was to establish the relationship of certain basic motor abilities and morphological characteristics and efficacy in specific table tennis tasks. The research sample consisted of cadet category table tennis players (N=101; aged 10.52±0.78 years, training experience 2.8±0.93 years). The participants were measured as they performed 24 motor tasks ,along with 15 anthropometric measures and 3 specific table tennis tests. Indicators of the relationship between morphological characteristics and motor abilities, coupled with the results of the specific table tennis tests indicate that: a) subcutaneous fatty tissue on the lower extremities significantly limits the test results where movements involving fast changes in direction are required; b)subcutaneous abdominal adipose tissues have a positive influence on tasks demanding controlled and precise alternate bouncing of the ball; c) in general, a positive influence can be seen in the results of specific tests concerning the following motor abilities: arm coordination, agility, explosive arm power, movement frequency speed and repetitive leg power. The test used for a coordination assessment of the whole body revealed a negative influence on the success of performing specific tasks.